PERANCANGAN PENGELOLAAN BADAN USAHA MILIK DESA BERBASIS SYARI’AH - Adinta Oktaningrum Pramesty; Shita Tiara; Ardhansyah Putra Hrp (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2020)
One of the ways to manage the economy of the village community is to form a Village-Owned Enterprise (BUMDes). The Village Government hoped that BUMDes could develop community independence and strengthen the village economy by increasing Village Original Income. BUMDes business results would be used for village interests such as village development and village community empowerment. Sei Limbat Village was one of the villages that had the most Muslim population. It was estimated that 90% of the population were muslims. This study aimed to design the concept of business management based on the principles of shari’a in BUMDes Warohmah. This was because the majority of Sei Limbat villagers were Muslim and still had a strong mutual cooperation. This study used a qualitative method. Data was obtained through observation, interviews and documentation studies. Furthermore this data was analyzed by data reduction, data presentation and conclusion drawing. The results of this study indicated that shari’a accounting principles could be applied and implemented in the management of business units owned by BUMDes Warohmah. The application of BUMDes management principles that distinguish between conventional and sharia was the legal basis in force.